An Energy-Efficient Transmission Protocol for RNC-Based Cooperative WSNs with Partial Energy Harvesting Nodes - Yulun Cheng; Longxiang Yang (International Journal of Distributed Sensor Networks)
This paper addresses the energy-efficient transmission for the scenario of cooperative wireless sensor networks with partial energy harvesting (EH) nodes. A new EH decoding-recoding policy is proposed by regarding the EH constraints and the characteristics of random network coding. We develop an energy efficiency model to investigate the tradeoff mechanism between the saved energy and the waiting time of the EH node, through which the corresponding parameters in the policy are also optimized. Moreover, we propose a novel transmission protocol by embedding the considered policy in the opportunistic reception algorithm. The decoding failure probability is then derived to examine its transmission reliability. The obtained theoretical and simulation results indicate that the proposed protocol achieves superiority in energy efficiency; meanwhile, it can also provide similar transmission reliability under specific conditions, as compared to the conventional algorithms in the two-hop model.